Vidas e ilustrações de Santas penitentes desnudas, no deserto e em peregrinação,no Flos Sanctorum de 1513 - António José de Almeida (Universidade do Porto, 2009)
The attempt to identify a recumbent, half-naked female figure, which was recently discovered in a wall painting in the Church of Our Lady of Balsamão, in Chacim (Macedo de Cavaleiros, Trás-os-Montes), prompted the author of this paper to investigate the lives and illustrations of penitent naked female saints on Legendaries printed in Europe during the 15th and 16th centuries, with particular reference to the Iberian Peninsula, and specifically to the Flos Sanctorum em lingoagem portugues, printed in Lisbon at 1513. In them there are two kinds of naked female saints linked with penitential forms of life: those that lived in desert or uninhabited places (such as Saint Mary of Egypt or Saint Mary Magdalene), but also those that had went on pilgrimage (the three women of the Iberian legend of the Four Crowned Saints).In connection with his current subject of research, the author takes this opportunity of publishing also the results of his recent research in the field of prints illustrating the trifacial Holy Trinity holding the scutum fidei, and surrounded by the Evangelical tetramorph.